Training Based Organization Approach From Islamic Perspective - Ahmad, Mastura Binti; Bin Ahmad Razimi, Mohd Shahril (IKONOMIKA, 2018)
ABSTRACT The purpose of this paper is to present a concept inherent in Islam can be applied on the training. Training plays an important role in the organization without it the organization find difficulty to stay competitive in recent global world.Ongoing training is very important in an organization in order to compete and maintain excellent performance. This paper attempts to look at the concept and how to practice from the viewpoint of Islam. The study examines three concepts related to training (Itqan, al-Falahand Ihsan) and the principle of education Islam (Ta’dib) relating to the training.  Keywords: Concept of the training, principle of education Islam relating to training.